Perilaku Pencegahan dan Kondisi Jamban dengan Kejadian COVID-19 pada Lansia - Fitriana, Astri; Wijayanti, Yuni (Indonesian Journal of Public Health and Nutrition, 2023)
Background: The elderly have a high risk of being infected with COVID-19. The highest cases in Purbalingga Regency were in the area of Kalimanah Primary Healthcare Center, namely 2,268 cases. This research is to determine the relationship between prevention behavior and latrine condition with the incidence of COVID-19 in the elderly in the area of Kalimanah Primary Healthcare Center of Purbalingga Regency. Methods: This type of research is observational analytic with a case control design. The sample set is 36 cases and 36 controls using purposive sampling technique. The instrument used is a questionnaire, observation sheets, and meter. Bivariate analysis with chi square test. Results: The results showed that there was a relationship between COVID-19 prevention knowledge (p-value = 0,005), COVID-19 prevention attitude (p-value= 0,018), and hand washing practices (p-value= 0,033) with the incidence of COVID-19 in the elderly. There is no relationship between the practice of managing waste masks (p-value= 0,579), fruit and vegetable consumption (p-value= 0,443), physical activity (p-value= 0,777), and latrine condition (p-value= 0,593) with the incidence of COVID-19 in the elderly. Conclusion: Efforts are needed to increase education about the application of health protocols to prevent the transmission of COVID-19 in the elderly.